THE INFLUENCE OF VIDEO-BASED EDUCATION AND LEAFLETS ON IMPROVING FAMILY KNOWLEDGE AND ATTITUDES IN THE PREVENTION OF CORONARY HEART DISEASE - Elmukhsinur Elmukhsinur; Alice Rosy; Sety Julita; Heltty Heltty; Maria Magdalena (Poltekkes Kemenkes Jakarta III, 2026)
The prevalence of coronary heart disease in Indonesia continues to rise. Efforts to prevent coronary heart disease thru increasing family knowledge are very much needed. One of the efforts that can be made to increase family knowledge is thru health education using video media and leaflets. Research discussing the influence of educational media such as videos and leaflets on family knowledge in the prevention of heart disease is still limited. In addition, based on interviews with several family members in Tanah Datar Village, they stated that they have never received information about PJK prevention thru videos and leaflets. The number of people with hypertension and diabetes mellitus, which are risk factors for cardiovascular disease, is also quite high. The purpose of this study is to determine the effect of video- and leaflet-based education on improving families’ knowledge and attitudes regarding the preventionn of CHD. This research is an experimental study with a One group pre-test-post-test design approach. The sample size is 105 participants. Data analysis was performed using SPSS with a Paired Sample T-Test. A p-value of < 0.05 was considered statistically significant. The average knowledge score before the intervention was 53.41, and after the intervention, it was 84.49, with a p-value of 0.000. The average attitude score before the intervention was 22.70, and after the intervention, it was 33.90, with a p-value of 0.000. The intervention of health education videos and leaflets significantly improved the family’s knowledge about CHD prevention and their attitudes towards preventive actions.